Three new species of the leafhopper genus Drabescus Stål (Hemiptera: Cicadellidae: Deltocephalinae) from China - Wang, Jia-Jia; Qu, Ling; Xing, Ji-Chun; Dai, Ren-Huai (Zootaxa, 2016)
Three new species of leafhoppers: Drabescus cuspidatus sp. nov., Drabescus convolutus sp. nov. and Drabescus multidentatus sp. nov. are described and illustrated from China. A key to 24 of the 30 known Chinese species of the genus is given. The type specimens of the new species are deposited in the Institute of Entomology, Guizhou University, Guiyang, China (GUGC).